Central Australian Songs: A History and Reinterpretation of their Distribution through the Earliest Recordings. Issue 2 (July 2015) - Gibson, Jason
Abstract This paper contains a discussion of an unpublished essay by TGH Strehlow concerning the historic wax cylinder recordings of songs from Central Australia made by Walter Baldwin Spencer and Frank Gillen in 1901. The manuscript, written by Strehlow in 1968, begins with an explanation of the historical context of the song recordings, and the distribution of song and dance traditions across the Australian inland. Strehlow elucidates the content via information imparted to him by a number of Arrernte and Luritja men, who first heard these recordings over 50 years after they were made, in 1960. Their explanation of these songs reveals further information on the diffusion of song verses across vast regions in Central Australia (including Warumungu, Anmatyerr, Arrernte, and Warlpiri country), and the incorporation of European words and themes within altharte (public) songs in which men sing and dance. I have expanded Strehlow's information on Spencer's recordings further with additional information from other ethno‐historical sources and my own contemporary fieldwork. Combined, this research deepens the anthropological understanding of some of the earliest ethnographic sound recordings ever made in Australia.